Analyzing the relationship between board characteristics and the activation of forensic accounting practices to enhance financial integrity: an applied study on Palestine Stock Exchange companies (Economic studies journal, 2025)
This study aimed to analyze the relationship between board characteristics (such as independence, size, professional certifications, academic specializations) and the activation of forensic accounting practices, and their role in enhancing financial integrity in companies listed on the Palestine Stock Exchange. The study relied on an applied approach that combined quantitative tools (such as a questionnaire) and the analysis of indicators from published financial data, allowing for measuring the relationship between directly observable characteristics and others derived from estimates by professional categories. This combination of data sources represents an important methodological contribution that comprehensively reflects the reality of the relationship between governance and forensic accounting. The study population included financial employees working in these companies listed on the Palestine Stock Exchange, while the sample consisted of (127) members. The following statistical methods were used: correlation and regression.Among the most prominent findings was the presence of a statistically significant positive relationship between board characteristics and the activation of forensic accounting practices. Forensic accounting positively impacts the enhancement of financial integrity. Characteristics such as member diversity, the presence of non-executive members, and the number of board meetings were more influential in enhancing oversight. The most prominent obstacles limiting the practical implementation of forensic accounting include weak professional competence and a lack of supportive legislation. The study also recommended developing legislation specific to forensic accounting, enhancing the independence and diversity of boards of directors, training financial personnel on forensic accounting tools and methods, and expanding the role of audit committees.
Keywords: Board of Directors Characteristics; Forensic Accounting; Financial Integrity